How films affect tourist's perception and motivation to travel / Siti Aisyah Nadia Abdul Rahim and Nurul Syuhada Abd Rahim - Abdul Rahim, Siti Aisyah Nadia; Abd Rahim, Nurul Syuhada (2015)
The research is aim to study on how films affected tourist decision making towards perception and motivation. The objective of the study is to understand perceptions on film tourism among higher education students, to explore travel motivation and perception of film tourism and to further explore the extent of travel motivations based on physical places, storyline, castings and special events featured on films. The population among students who studied in Malacca where the researcher mainly focuses at UiTM Bandaraya Melaka. The researcher used questionnaire data collection method to study the film tourism influences in promoting destinations. A total number of 50 respondents were distributed to the students. The questionnaires were collected right after the respondents completed the survey forms. The survey is undertaken throughout May2015. The results revealed that and research objective where the effectiveness of the film tourism has being justified where most respondents were agreed that film tourism influence their perception and motivation to make decision to travel. Therefore this new phenomenon could create more excitement in promoting product and services offered yet effective and efficient.